Acclimatization and performance evaluations of sweetpotato (Ipomoea batatas L. Lam) on yield and yield components in different agro-ecologies of Northern Ethiopia - Lamaro, Gloria Peace (Journal of Dryland Agriculture, 2020)
The study is aimed at evaluating the genotype by environment interactions (GEI) on acclimatization of sweetpotato genotypes to the farmers’ field conditions. A field evaluation was done on six sweetpotato genotypes planted in RCBD, three replications in three different agro-ecologies. These genotypes were previously (2012, 2014) tested for yield performance in the same environment. Data collected were subjected to ANOVA. Genetic merit and GEI for total storage root tuber yield (TSRTY) was tested using BLUPs and GGE biplot, respectively. Clustering of genotypes was done using Ward’s linkage method in the Squared Euclidean distance. Breeding significance and distance among clusters was determined using Mahalanobis’s distance. Environment played significant (P<0.01) role in determining the genotypes’ maturity days; and genotypes in lowland matured earlier than those on higher altitudes. TSRTY ranged from 7.5 to 59.5 t/ha, and total fresh biomass (TFB) 21.6 to 36.0 t/ha. Genotypes with high harvest index produced high TSRTY, TFB and NNPP hence well acclimatized. GEI was responsible for the genotypes acclimatization in the studied agro-ecologies; Tulla and Kulfo demonstrated wide acclimatization while Berkume was specific. Cluster II with very high dry matter content may be explored for crossbreeding cluster I and III to produce OFSP transgressive segregants for Ethiopia.